KEPEMIMPINAN KEPALA MADRASAH DALAM INOVASI MANAJEMEN PENDIDIKAN DI MA SIROJUT THOLIBIN RACEK TIRIS PROBOLINGGO - Rifa'i, Taufiqurrohman; Efendi, Hudrat (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2019)
ABSTRACT In the current era of globalization, education is one of the obligations that must be taken by personal and social that can not be negotiable. Because basically education is a social process that aims to develop the potential of human life in order to face the demands of the age in the future, along with the development and changing times that are increasingly shifting. Educational management is the study of how to organize resources to achieve goals that have been set productively and how to create a good atmosphere for people who participate in achieving agreed goals. In relation to the development of education, the madrasa head has a very important role and task. This is because the headmaster of a madrasa as a leader is one of the factors driving the progress of the world of education. This means that the headmaster is required to have the ability to carry out educational innovations that are no longer relevant to current conditions for the achievement of national and state development. While the things that must be considered for the head of madrasa in carrying out their duties should the principal really be able and mastered both theoretically and practically, in providing guidance to all his subordinates should be accompanied by concrete examples so that they can further spur motivation, innovation should be at MA Sirojut Tholibin Probolinggo Tiris Racek is planned far in advance. While teachers if there are problems in the teaching and learning process should seek solutions with other teaching staff, they should be able to further enhance their abilities in preparing themselves to face the possibilities that might occur. Tiris Probolinggo, before implementing educational programs should seek clarity and direction of the goals of these programs. Keywords: Madrasah Principals Leadership, Educational management innovation